1971
DOI: 10.1021/ja00741a058
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and crystallographic characterization of bis(tetramethylammonium) carbidohexadecacarbonylhexaferrate, a hexanuclear carbidocarbonyl derivative of iron

Abstract: 7 2 ir5* at 273 nm (/ = 0.29), and m -5* at 232 nm (/ = 0). These Xmax values are in good agreement with the observed spectrum of hexaphenylpentalene1 23456 (Xx 720 nm (log e 1.95), X2 380 nm (log e 3.99), and X3 310 nm (log e 4.52)) if one assumes that the presence of the phenyl groups shifts each peak to lower energy ( 14) There is some uncertainty as to whether the 285-nm band is due to methylpentalene or to its dimer.'

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

1972
1972
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(52 citation statements)
references
References 0 publications
1
51
0
Order By: Relevance
“…15,36 We reproduced this RT structure with an R 1 value of 5.1%, solving in the space group Pnmb , a non-standard setting of Pnma , in order to facilitate comparison to LT . In the asymmetric unit of RT there are two independent iron anion clusters that are bisected by crystallographic mirror planes (thus one half of each is unique) and two independent tetramethylammonium cations with atoms in general positions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…15,36 We reproduced this RT structure with an R 1 value of 5.1%, solving in the space group Pnmb , a non-standard setting of Pnma , in order to facilitate comparison to LT . In the asymmetric unit of RT there are two independent iron anion clusters that are bisected by crystallographic mirror planes (thus one half of each is unique) and two independent tetramethylammonium cations with atoms in general positions.…”
Section: Resultsmentioning
confidence: 99%
“…15 The 13 C NMR spectrum of the compound was not reported in that paper, but we recorded it in order to verify the presence of a central carbide. 13 C{ 1 H} NMR (125.7 MHz, THF- d 8 ): δ 56 (CH 3 ), 229 (CO), 485 (C 4− ) ppm.…”
Section: Methodsmentioning
confidence: 99%
“…9a) was studied in the early 1970’s as a model of possible intermediates in the iron-catalyzed Fischer-Tropsch process. 129,130 In collaboration with DeBeer, we recently reported more extensive crystallographic characterization of 19 , as well as X-ray emission studies that elucidated the electronic structure of the iron-carbide core and demonstrated the delocalized orbitals that give rise to Fe-C bond-ing. 145 Oxidation of 19 leads to related Fe 5 and Fe 4 carbide/carbonyl clusters.…”
Section: Carbide Complexes and Fe-n2 Complexes With Carbon Ligandsmentioning
confidence: 99%
“…A host of iron-carbonyl clusters have been synthesized with a variety of bridging (≥ μ 3 ) single atom ligands, including μ 6 -C clusters, such as [(μ 6 -C)Fe 6 (CO) 16 ] 2− , with arrangements reminiscent of the FeMoco structure (Figure 1B, see SI for a comprehensive list). 5 While a related cluster has been reported displaying a μ 6 -N ligand, [( μ 6 -N)Fe 6 (CO) 15 ] 3− , with potential for structure function studies of the effect of the interstitial ligand, changes in the structure and number of CO ligands complicates interpretations. In the cases where completely isostructural clusters can be prepared with bridging elements of the second row of the periodic table, the large number (≥ 9) of diatomic ligands limits interpretations regarding the activation of a single small molecule substrate, which is most relevant to biological systems.…”
Section: Introductionmentioning
confidence: 99%